Aplicación de la propuesta sobre la construcción de pensamiento lectoescrito - Hernandez, Isabel; Rubio, Dora; Latorre, Raquel; de Parra, Ammy; Palencia, Lilia; Perdomo, Amparo; Luna, Elvira; Alonso, Ofelia; Ordoñez, Nydia; Gonzalez, Mercedes (Nodos y Nudos, 2012)
Aplicación de la propuesta sobre la construcción de pensamiento lectoescrito